Biodiversité, restauration écologique et intensification écologique : quelles imbrications ? - Daouda Ngom (VertigO)
Biodiversity is a global concept that implies the variety and variability of the living being at all levels of organization, from the gene to the ecosystem. It now appears that the Earth's ecosystems have been significantly transformed by human activities, resulting in a permanent threat to biodiversity. The fragmentation of natural ecosystems such as forests has a definite impact on the relationship between man and wild animals, leading to the proliferation of zoonoses. This erosion of biodiversity has become a global problem from an ecological, socio-economic and health point of view, which questions the modes of development of human activities. To reduce or annihilate the degradation process of natural ecosystems, ecological restoration, defined as an intentional action aimed at the self-healing of degraded ecosystems, has flourished around the world. This concept has an epistemological kinship with the notion of ecological intensification defined as a process of transformation of productive ecosystems that must be realized within the limits of all viability of a given ecosystem. Thus, it appears necessary today, to save the planet from the excesses of conventional agriculture, to promote the ecological intensification of agriculture and the ecological restoration of degraded ecosystems.